Effectiveness of Octopus (Octopus sp.) Ink Exctract on the Growth of Catfish (Clarias sp.) Infected with Aeromonas hydrophila - Saputra, Marta Ade; Scabra, Andre Rachmat; Affandi, Rangga Idris (Aquaculture Department, University of Mataram, 2025)
One material that can be used to improve feed quality is octopus ink. Octopus ink can serve as an alternative nutrient source to optimize catfish growth. Ink produced by cephalopods such as squid, octopus, and cuttlefish contains various components, including fat, protein, ash, and carbohydrates. The aim of this research is to determine the effect of administering octopus ink extract (Octopus sp.) on the growth of catfish (Clarias sp.) infected with Aeromonas hydrophila bacteria. The method used in this research was experimental, involving five treatments with three replications: treatment 1 (Control/P1), treatment 2/P2 (40 ml/kg), treatment 3/P3 (80 ml/kg), treatment 4/P4 (120 ml/kg), and treatment 5/P5 (160 ml/kg). The research steps included octopus ink extraction, a Lethal Concentration 50 (LC50) test, preparation of tools and materials, supplementation of octopus ink extract in feed, application of test treatments, challenge tests with Aeromonas hydrophila, and maintenance. The results of this research showed that treatment 5 (160 ml/kg) yielded the best outcomes in growth parameters, including an absolute weight of 1.26 grams, a specific growth rate of 0.57%/day, a feed convertion ratio (FCR) of 1.66, and a survival rate of 90%.